Creating Human Insecurity: The National Security Focus in Canada’s Immigration System - Lowry, Michelle (Refuge: Canada's Journal on Refugees, 2002)
This paper explores the processes through which Canada’s immigration system creates human insecurity for newcomers to Canada. With a focus on the new Immigration and Refugee Protection Act and post-September 11 security measures such as the Safe Third Country Agreement, I argue that the immigration system draws on and reaffirms national security discourses. Measures designed to create national security, in turn, create human insecurity for migrants and refugees. Using a feminist approach that explores how gender, race, and class oppressions intensify experiences of in/security, this paper suggests that the new national security measures within Canada’s immigration system will likely have a disproportionate impact on classed, raced, and gendered asylum seekers.